Surgical Treatment of Symptomatic Neuromas After Lower Limb Amputations - Liabakh, A.P.; Lazarenko, H.M.; Piatkovskyi, V.M. (TERRA ORTHOPAEDICA, 2020)
Summary. The pain after amputations is a global problem of modern medicine. There are three distinct clinical entities that can form the postamputation pain: phantom limb pain (PLP), phantom sensations (PSs), and residual limb pain (RLP). PLP and PSs are pathophysiological phenomena, which need complex conservative treatment. RLP is a local condition that arises from neuroma, excessive scarring, osteophites, etc. and can be resolved by surgery. Objective: to analyze the results of surgical treatment of patients with symptomatic neuromas after lower limb amputations (LLA). Materials and Methods. The study included 43 patients with symptomatic neuromas 3–10 years after LLA. There were 40 male and 3 female patients (mean age 33.9±3 years). Amputations were caused by trauma (33 cases), mine-blast injury (7 cases), diabetes (1 case), and oncology (2 cases). The level of amputation was thigh (3 cases), knee (1 case), and ankle (39 cases). The pain intensity was measured by the VAS (Visually Analog Scale) and prosthesis using by the ALAC (Artificial Limb and Appliance Centre, USA) scale. Results. RLP had 43 patients (100%), PLP – 8 (8.6%), and PSs – 35 (81.4%) patients. The average level of pain was 7.4±0.9. Prosthesis was used in 74.4% (32 patients), but 11 of them used prosthesis for cosmetic or transportation reasons (levels I and II by the ALAC scale). Complications after surgery were presented by hematoma (3 cases), marginal skin necrosis (2 cases), and tearing of m. gastrocnemius from the tibia after the fall on the stump (1 case). The results were assessed in 35 patients in terms from 1 to 15 years. The pain severity decreased from 7.4±0.9 to 3.2±0.6 (p˂0.05; two-sample t-test). The number of RLP cases decreased to 11 (31.4%), but the number of PLP and PSs cases did not significantly change (PLP – 5 cases or 14.3%; PSs – 27 cases or 77.1%). The prosthesis using rised to 100% due to functionality (III–VI levels by the ALAC scale). Conclusions. Surgical method is the main treatment of symptomatic neuromas after LLA. The surgery must expect proximal neurotomy and, if need, reamputation and stump reconstruction. This approach helps to reduce pain and improves the functional ability of persons with LLA.